Effect of increased training quality on response to ski training on snow in elite cross-country skiers - Rusko, H. K.; Paavolainen, L. M.; Vahasoyrinki, P.; Vaananen, I. (Medicine & Science in Sports & Exercise, 1997)
The effect of increased training quality on the training response to cross-country ski training when the volume of training was highest was investigated. Male elite skiers (N = 25) were divided into a control (N = 17) and quality (N = 8) groups. The quality group replaced 2.3 of an average 17 hours of training with "dry-land training" (running, circuit training, swimming, stretching, and ball games). The quality group's VO2max and maximal running treadmill performances improved significantly whereas the control group's did not. Neither group changed in resting testosterone, cortisol, creatine kinase, or myglobin concentration. It was concluded that: ". . . maximal anaerobic running power was related to the volume of 'dry-land training' (r = .49) and circuit training (r = .7) and the decrease in resting myoglobin concentration was related to the volume of 'dry-land training' (r = .6) and circuit training (r = .75). . . . the effects of ski training on snow can be improved by replacing a small part of it by nonspecific dry-land exercises to avoid muscular overload." Implication: This investigation endorsed the specificity of training principle in elite male skiers. When running activities were performed, running performances improved whereas those who only skied did not change in running performances. The conclusions of the study are misleading and unwarranted.